Crusaders for Fitness : The History of American Health Reformers - JAMES C. WHORTON (Princeton University Press, 2014)
ONE OP THE CLASSIC CHARACTERS BRED BY AMERICAN CULture of the past century and a half is the health fanatic, the man who (in Twain's phraseology) eats what he doesn't want, drinks what he doesn't like, and does what he'd druther not, all the while smugly announcing himself to be energetic, joyful, and certain of long life, and exhorting his errant neighbor to reform.1 The comic stature he has achieved is well deserved, but he has also a serious side that has been badly neglected. Until recently at least, historians have recognized health faddism primarily for its rich store of anecdotes for illustrating human credulity and the possibilities for distorting scientific thought. As a subject for serious intellectual history it has gone begging, except for scattered articles in scholarly journals and two recent book-length studies: Ronald Numbers, Prophetess of Health: a Study of Ellen G. White, and Stephen Nissenbaum, Sex, Diet and Debility in Jacksonian America: Sylvester Graham and Health Reform. Those volumes are valuable but still leave much room for elaboration on health faddism as an evolving, persistent phenomenon in American society